1982
DOI: 10.1021/jm00351a007
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazolo[3,4-d]pyrimidine ribonucleosides as anticoccidials. 2. Synthesis and activity of some nucleosides of 4-(alkylamino)-1H-pyrazolo[3,4-d]pyrimidines

Abstract: Pyrazolo [3,4-d]pyrimidine Ribonucleosides as Anticoccidials. 2. Synthesis and Activity of Some Nucleosides of 4-(Alkylamino)-lff-pyrazolo [3,4-d]pyrimidines

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Sometimes, the released nucleobase from the glycosyl donor binds more strongly with the enzyme than the acceptor base, which results in competitive inhibition (26). The problem of inhibition can be solved by using a coupled enzymatic system, e.g., pyrimidine and purine nucleoside phosphorylase together with a pyrimidine nucleoside as the glycosyl SCHEME 1 donor and a purine base as the acceptor, since the released pyrimidine base does not inhibit the purine nucleoside phosphorylase (Scheme 3) (27)(28)(29)(30).…”
Section: Glycosyl Transfer Reactions Catalyzed By Nucleoside Phosphormentioning
confidence: 99%
“…Sometimes, the released nucleobase from the glycosyl donor binds more strongly with the enzyme than the acceptor base, which results in competitive inhibition (26). The problem of inhibition can be solved by using a coupled enzymatic system, e.g., pyrimidine and purine nucleoside phosphorylase together with a pyrimidine nucleoside as the glycosyl SCHEME 1 donor and a purine base as the acceptor, since the released pyrimidine base does not inhibit the purine nucleoside phosphorylase (Scheme 3) (27)(28)(29)(30).…”
Section: Glycosyl Transfer Reactions Catalyzed By Nucleoside Phosphormentioning
confidence: 99%
“…agents is limited due to the rapidly developing drug resistance in conjunction with the unsatisfactory status of present treatments of bacterial and fungal infections [3,4]. Pyrimidine nucleus has gained potential importance in medicinal chemistry, as some of its derivatives exhibited a wide range of biological activities, such as antiviral [5][6][7][8], anticoccidials [9,10], antimicrobial [11][12][13][14], antitumor [15][16][17][18], herbicidal, antileukemic [19,20], pesticides [21], CNS agents [22], tuberculostatic [23][24][25], antileishmanial [26][27][28], radioprotectant [29], anti-in ammatory [30], and cardiovascular activities [31,32]. The biological signicance of the above heterocycle prompted us to explore the synthesis of novel pyrimidines from 3-amino-2-methyl-5,6, 7,8-tetrahydrobenzo [4,5] The asymmetric unit of the title compound contains one independent molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrazoloij3,4-d]pyrimidine derivatives demonstrate various biological activities, such as inhibition of phosphodiesterase-5 (PDE-5), 5 modulation of the human adenosine receptor, 6 antiviral, 7 anticoccidial, 8 antimicrobial, 9 etc. These investigations revealed that substitution of various groups on the ring imparts different activities.…”
Section: Introductionmentioning
confidence: 99%